Habituation of Fair Attitude in Elementary School Mathematics Learning - Syafaatun, Alifiah; Sutama, S (Universitas Muhammadiyah Surakarta, 2023)
Purpose: This research aims to 1) elaborate a fair attitude in the preliminary activities. 2) Describe a fair attitude in core activities. 3) Exploring a fair attitude in the closing activities of mathematics learning. Methodology: This research uses a qualitative method with an ethnographic approach. Data collected through observation and interviews. The research subjects were students and mathematics teachers. Data analysis technique using plot method. Results: The learning activities in question are introduction, core, and closing. Fair attitudes that are familiarized through each learning activity have an impact on children and the learning environment. Applications/Originality/Value: The phenomenon of discrimination still happens in the school environment because teachers do not protect their students. Nurturing students can be done by teachers through a fair attitude. The application of a fair attitude by teachers can be done in every step of learning to foster student confidence. Confidence will make the learning process occur optimally so that learning objectives can be achieved. The peer teaching method is applied as a form of a fair attitude that facilitates students according to their abilities.